(untitled) - McCarthy, Michael (Cambridge, 2002)
This new reference and practice book looks at the most colourful and fun area of vocabulary - idioms. This material will appeal to students from intermediate level upwards who want to understand the English which native speakers really use day to day. Over 1000 of the most useful and frequent idioms which learners are likely to encounter are presented and practised in typical contexts, so that by the end of the book learners will have hundreds of idioms 'at their fingertips'. English Idioms in Use will help you 'get off to a flying start'!
Keywords: English language,English language; Idiom